Three new species of Lauraceae from the Atlantic rainforest of Brazil - Rodrigues De Moraes, Pedro Luis [UNESP]; Vergne, Matheus Carvalho [UNESP]; van der Werff, Henk (Magnolia Press, 2017)
Three South-American new species belonging to Cinnamomum, Mezilaurus, and Williamodendron, are described and illustrated from specimens collected in the Atlantic rainforest of Brazil. The new species are Cinnamomum baitelloanum, Mezilaurus sessiliflora, and Williamodendron itamarajuensis. Their putative relationships within the respective genus are discussed.
Keywords: Bahia; Cinnamomum; Espirito Santo; Mezilaurus; new species; Williamodendron